Lung Cancer Detection Using Deep Learning (International Journal of Food and Nutritional Sciences, 2022)
Cancer is a disease in which the body's cells multiply uncontrollably. When referring tocancer that starts in the lungs, the term "lung cancer" is used. Lung disease is among themost prevalent illnesses that are impacted the initial phases of treatment to improve patientsurvival rates. Lymph nodes or other bodily organs may become affected by lung canceronce it has progressed from the lungs. Pulmonary cancer, also referred to as lungcarcinomas the main reason for cancer-related deaths worldwide. By identifying malignancythat has not yet spread, computed tomography (CT) has the potential to avert hundreds ofthousands of fatalities each year. A powerful and emerging technique for feature learningand pattern identification is deep learning. In this research, we developed a convolutionalneural network model for the detection of lung cancer. According to our findings, Lungcancer is treated with convolutional neural networks diagnosis more often than other deeplearning techniques.